Flame-retardant multifunctional polyvinyl alcohol / phytic acid / charcoal composite film and preparation method thereof

Through the preparation of PVA/PA/BC composite film, the synergistic effect of PA and BC is used to solve the problems of harmfulness, poor toughness and insufficient water resistance of flame retardants, high toughness and excellent flame retardant performance are achieved, and PVA materials are expanded scope of application.

CN119176999AInactive Publication Date: 2024-12-24NINGBO UNIV

Patent Information

Application Number
CN202411699572.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The flame retardant in existing flame retardant PVA films is harmful to the human body, has poor material toughness and poor water resistance, which limits its application in construction and other fields.

Method used

Polyvinyl alcohol (PVA)/phytic acid (PA)/biochar (BC) composite film is used to adjust the pH value of PA and pretreat BC to form an activated porous structure, which improves the flame retardant performance and toughness of the composite material. , and prepare films by solution casting method to simplify the process flow.

Benefits of technology

It has achieved high toughness, water resistance and excellent flame retardant performance, and the flame retardant level reaches V-0, reducing environmental pollution, and expanding the application of PVA materials in electronic devices, building materials and packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176999A_ABST
    Figure CN119176999A_ABST
Patent Text Reader

Abstract

The invention discloses a flame-retardant multifunctional polyvinyl alcohol / phytic acid / biochar composite film and a preparation method thereof. The flame-retardant multifunctional polyvinyl alcohol / phytic acid / biochar composite film comprises the following components in parts by mass: 100 parts of polyvinyl alcohol, 5-15 parts of phytic acid, 2-10 parts of biochar, 0.3-1 part of a stabilizer, 0.5-0.8 part of a plasticizer, 0.5-0.7 part of a lubricant and 0.3-1 part of a compatibilizer. The biochar and the phytic acid are compounded with the polyvinyl alcohol, so that the polyvinyl alcohol can be reinforced, and the flame retardant property, the toughness and the water resistance of the polyvinyl alcohol are improved. The phytic acid is used for pretreatment in the biochar activation process, the biochar is endowed with flame retardant property, and a specific coated core-shell structure is formed through the pre-dispersion process of the phytic acid and the biochar, so that the dispersity and stability of the biochar in a polyvinyl alcohol matrix can be improved. According to the method, the flame retardance, toughness and water resistance of the product are improved, the cost is low, preparation is easy, meanwhile, the preparation technological process is simple and convenient, the equipment requirement is low, pollution to the environment is small, and wide application prospects and market value are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame-retardant plastic films, and in particular is a polyvinyl alcohol / phytic acid / biochar composite film and a preparation method thereof. Background Art

[0002] Polyvinyl alcohol (PVA) is a low-cost, non-toxic, biodegradable polymer with good gas barrier properties, solvent resistance, biocompatibility and other advantages. It is mostly used to prepare composite films for packaging. However, there are some defects in PVA materials that limit its application. First, PVA is a flammable substance - due to its composition and chemical structure, its limiting oxygen index is relatively low. At the same time, PVA will produce a lot of black smoke and dripping droplets when it burns, which greatly limits its practical application in construction and other fields. Second, PVA has limited toughness - PVA is prone to cracking during processing, and its relatively low elongation poses challenges to film production. Third, the high hydroxyl content in PVA makes it sensitive to water - PVA will swell and dissolve when in contact with water, which affects its application in humid environments.

[0003] Adding flame retardants is the main way to modify PVA flame retardant. Among them, halogen flame retardants will produce a lot of smoke and release hydrogen halide gas during combustion, causing serious environmental pollution and threatening health. Therefore, halogen-free flame retardants are usually selected for flame retardant modification of PVA, among which bio-based materials such as phytic acid (PA), chitosan and tannic acid have attracted widespread attention due to their environmental friendliness. If nitrogen-based flame retardants such as chitosan are used alone, a large addition amount (>25 wt%) is usually required to achieve a high flame retardant efficiency. In addition, PVA lacks compatibility with nitrogen-based flame retardants, which affects the mechanical properties of PVA composites. It is worth noting that the six phosphate groups on the PA molecule contribute to the formation of fixed carbon, thereby improving the flame retardancy of PVA. PA can not only be used as a phosphorus-based flame retardant with good biocompatibility and degradability, but its phosphate group has a plasticizing effect on PVA, which can improve the toughness of the material. In view of this, how to apply PA to PVA materials to improve the toughness of PVA while improving the flame retardant effect is worth further exploration.

[0004] Adding reinforcing fillers such as graphene oxide, montmorillonite, carbon nanotubes, biochar and cellulose to PVA can effectively improve its mechanical properties, thermal stability and water resistance, thereby expanding the application range of PVA. Among them, biochar (BC) is a low-cost, porous structure, and large specific surface area carbon-rich material. Some studies have reported the reinforcing effect of BC on PVA composites. For example, Mozrall et al. (Sustain. Chem. Pharm. 2023, 35, 101223) found that BC with different dosages and particle sizes improved the strength and toughness of composite materials to varying degrees. At the same time, Marco et al. (Polymers 2020, 12, 811) reported a PA / BC flame retardant system for cotton fabrics, in which BC, as an excellent carbon source, undergoes thermochemical conversion in an environment with limited oxygen, and forms a dense carbon layer under the synergistic effect of PA, which prevents further combustion and decomposition, thereby significantly improving the flame retardant properties of the material. Although the flame retardant system of PA / BC has a good flame retardant effect on cotton fabrics, it has not been specifically applied in the flame retardant modification of polymers. Therefore, the process of applying PA / BC to PVA film is more challenging. In addition, the patent application document with announcement number CN100516325C discloses a method for preparing a flame retardant melamine formaldehyde resin / PVA flame retardant fiber, using melamine and formaldehyde as flame retardants, and an acidic saturated sodium sulfate aqueous solution as a coagulation bath, and obtaining a melamine formaldehyde resin / PVA flame retardant fiber through certain processing means. The process of preparing a flame retardant PVA composite material by this method is cumbersome, the selected flame retardant has certain toxicity, and causes great environmental pollution. At the same time, the water resistance of the material is unclear.

[0005] In order to improve the flame retardant properties, toughness and water resistance of PVA composite films, expand their application range, simplify the preparation process and reduce environmental pollution, it is urgent to invent a simple method for preparing a flame retardant PVA multifunctional composite film to expand the application of PVA in the field of environmentally friendly flame retardant materials. Therefore, the present invention proposes a flame retardant multifunctional PVA / PA / BC composite film and a preparation method thereof. Summary of the invention

[0006] The problem to be solved by the present invention is that, in view of the problems that the flame retardant in the existing flame retardant PVA film is harmful to the human body, the material has poor toughness and poor water resistance, a flame retardant multifunctional PVA / PA / BC composite film and a preparation method thereof are proposed.

[0007] The technical solution adopted by the present invention to solve the above technical problems is: a flame-retardant multifunctional PVA / PA / BC composite film, whose mass parts are as follows: 100 parts of PVA, 5-15 parts of PA, 2-10 parts of BC, 0.3-1 parts of stabilizer, 0.5-0.8 parts of plasticizer, 0.5-0.7 parts of lubricant, and 0.3-1 parts of compatibilizer.

[0008] Preferably, the PVA model is at least one of 0599, 1799, and 2499, and the polymerization degrees thereof are 500, 1700, and 2400, respectively, and the alcoholysis degree is 99 mol%.

[0009] Preferably, the BC is derived from one or a combination of two or more of pine, poplar, eucalyptus, oak, and bamboo, and is pyrolyzed at 300-500°C in an oxygen-deficient environment for 3-5 hours, and then washed, dried, and crushed to obtain particles. Preferably, the PA is a 70% PA aqueous solution.

[0010] Preferably, the stabilizer is one of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant 1790, or a combination of two or more thereof.

[0011] Preferably, the plasticizer is at least one of sorbitol, xylitol, erythritol and lactitol.

[0012] Preferably, the lubricant is at least one of calcium stearate, erucamide, stearamide and zinc stearate.

[0013] Preferably, the compatibilizer is at least one of glycidyl methacrylate, L-lysine triisocyanate, maleic anhydride grafted ethylene-octene copolymer, glycidyl methacrylate grafted ethylene-octene copolymer and ethylene-vinyl acetate copolymer.

[0014] The method for preparing the flame-retardant multifunctional PVA / PA / BC composite film comprises the following steps:

[0015] 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0016] 2) Grind the BC particles and pass them through 100 mesh, 1000 mesh, 2000 mesh and 3000 mesh sieves to obtain BC samples with different particle sizes;

[0017] 3) The BC samples with different particle sizes obtained in step 2) were mixed with 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:8-12, stirred for 1-2 h, filtered, and then dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture, which was fully stirred and the pH value of the solid-liquid mixture was adjusted to 5.5-6 using the PA solution. The mixture was then ultrasonically treated for 10-20 min, the solid-liquid mixture was filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900°C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC;

[0018] 4) adding 5 to 15 parts of PA solution and 2 to 10 parts of BC obtained in step 3) to 50 parts of deionized water, and ultrasonically treating for 10 to 30 min to obtain a pre-dispersed PA and BC mixed aqueous solution;

[0019] 5) Mix 100 parts of PVA with 400-600 parts of deionized water, heat and stir at 85-95°C until completely dissolved, add 0.3-1 parts of dried stabilizer, 0.5-0.8 parts of plasticizer, 0.5-0.7 parts of lubricant, and 0.3-1 parts of compatibilizer, and continue heating and stirring at 85-95°C for 1-2 h to obtain a PVA mixed solution;

[0020] 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), stirring and mixing at 85-95° C. for 1-2 h to obtain a PVA / PA / BC mixed solution;

[0021] 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method. The mixed solution was poured into a culture dish, and after air-drying at room temperature for 30 to 60 min, the culture dish was placed in an oven at 65° C. and continued to dry for 20 to 48 h, and finally a PVA / PA / BC composite film with a thickness of 0.05 to 0.50 mm was obtained.

[0022] Preferably, in step 2), BC is screened starting from the smallest pore size, in the order of 3000 mesh, 2000 mesh, 1000 mesh and 100 mesh; and in step 3), the heating rate of the muffle furnace is 5-20°C / min.

[0023] BC has a porous structure and a high specific surface area. After being uniformly dispersed during the preparation of PVA composite materials, it can achieve a good particle reinforcement effect and improve the mechanical properties of the composite material. In the above method step 3) of the present invention, BC is treated at high temperature to reduce the oxygen-containing functional groups on its surface, increase the specific surface area, and activate BC while forming a porous structure and a partially graphitized structure, thereby increasing the reinforcement effect of BC on the PVA composite film. Using PA to adjust the pH value not only neutralizes potassium hydroxide, but also pre-treats BC, increasing the content of phosphorus with a flame retardant effect.

[0024] The technical solution of the present invention provides a flame-retardant multifunctional PVA / PA / BC composite film and a preparation method thereof, wherein the PVA in the composite film is a biodegradable and environmentally friendly polymer; PA is a bio-based flame retardant, which is an organophosphorus compound extracted from plant seeds and has the advantages of low cost, non-toxicity, and good biocompatibility; BC has the advantages of a porous structure, a large specific surface area, and the like, and is also a high-quality carbon source.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. In the process of BC activation, the present invention uses PA to adjust the pH value of BC, which not only neutralizes the unreacted potassium hydroxide, but also pre-treats BC, increases the content of phosphorus, and gives BC flame retardant properties. This process not only reduces the use of reagents, but also facilitates the subsequent flame retardant modification of PVA / PA / BC composite films.

[0027] 2. In the process of the present invention, by the pre-dispersion process of PA and BC in step 4), PA can enter the porous structure of the activated BC in advance to form a specific coated core-shell structure, and PA has good compatibility with the PVA matrix. The pretreatment process can improve the compatibility of BC and PVA, which is beneficial to the uniform dispersion and stability of BC particles in the PVA matrix, and improves the performance of the PVA / PA / BC composite material.

[0028] 3. Compared with the preparation method of the traditional flame-retardant PVA composite film, the PVA / PA / BC composite film prepared by the method of the present invention has the advantages of excellent flame retardancy, high toughness, water resistance, etc., and the flame retardancy grade can reach V-0. PA and BC in the method of the present invention are both biomass materials, low cost and easy to prepare. At the same time, the preparation process is simple, the equipment requirements are low, and the environmental pollution is small. It is expected to expand the application of PVA materials in the fields of electronic devices, building materials, packaging materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The tensile properties of PVA / PA / BC composite films with different BC addition amounts;

[0030] Figure 2 The hygroscopic properties of PVA / PA / BC composite films with different BC addition amounts;

[0031] Figure 3 is the limiting oxygen index of PVA / PA / BC composite films with different BC addition amounts;

[0032] Figure 4 This is a surface scanning electron microscope image of the PVA / PA / BC composite film of Example 3;

[0033] Figure 5 To study the tensile properties of PVA / PA / BC composite films with different BC mesh numbers;

[0034] Figure 6 To study the hygroscopic properties of PVA / PA / BC composite films with different BC mesh numbers;

[0035] Figure 7 The limiting oxygen index of PVA / PA / BC composite films with different BC mesh numbers added;

[0036] Figure 8 are scanning electron microscope images of BC with different mesh sizes, among which, Figure 8 (a) is 100 mesh, Figure 8 (b) is 1000 mesh, Figure 8 (c) 2000 mesh, Figure 8 (d) 3000 mesh;

[0037] Fig. 9 The tensile properties of PVA / PA / BC composite films with different PA addition amounts;

[0038] Fig.10 The hygroscopic properties of PVA / PA / BC composite films with different PA addition amounts;

[0039] Fig.11 The limiting oxygen index of PVA / PA / BC composite films with different PA addition amounts;

[0040] Fig.12 The tensile properties of PVA / PA / BC composite films with different amounts of stabilizer added;

[0041] Fig.13 The hygroscopic properties of PVA / PA / BC composite films with different amounts of stabilizer added;

[0042] Fig.14 The limiting oxygen index of PVA / PA / BC composite films with different stabilizer addition amounts;

[0043] Fig.15The tensile properties of PVA / PA / BC composite films with different plasticizer addition amounts;

[0044] Fig.16 The hygroscopic properties of PVA / PA / BC composite films with different amounts of plasticizer added;

[0045] Fig.17 is the limiting oxygen index of PVA / PA / BC composite films with different plasticizer addition amounts;

[0046] Fig.18 The tensile properties of PVA / PA / BC composite films with different amounts of compatibilizer added;

[0047] Fig.19 The hygroscopic properties of PVA / PA / BC composite films with different amounts of compatibilizer added;

[0048] Fig. 20 is the limiting oxygen index of PVA / PA / BC composite films with different amounts of compatibilizer added;

[0049] Fig.21 This is a surface scanning electron microscope image of the PVA film of Comparative Example 1. DETAILED DESCRIPTION

[0050] The present invention is further described in detail below with reference to the accompanying drawings.

[0051] The mass fraction compositions of the PVA / PA / BC composite films of Examples 1 to 5 are shown in Table 1, and the PVA / PA / BC composite films of Examples 1 to 5 are numbered C1, C2, C3, C4, and C5, respectively, and a single factor experiment is performed.

[0052] Table 1

[0053]

[0054] In Examples 1 to 5, the stabilizer is antioxidant 1010, the plasticizer is sorbitol, the lubricant is calcium stearate, and the compatibilizer is glycidyl methacrylate.

[0055] The method for preparing the PVA / PA / BC composite film of Example 1 comprises the following steps:

[0056] 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0057] 2) Grind the BC particles and pass them through a 1000-mesh sieve to obtain a BC sample with a particle size of 1000 mesh;

[0058] 3) The BC sample obtained in step 2) was mixed with 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:10, stirred for 1 h, filtered, and then the BC was dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture. The solid-liquid mixture was fully stirred and the pH value was adjusted to 5.5-6 using the PA solution. The mixture was then ultrasonically treated for 10 min, filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900 °C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC.

[0059] 4) adding 10 parts of PA solution and 5 parts of BC obtained in step 3) into 50 parts of deionized water, and ultrasonically treating for 20 min to obtain a pre-dispersed PA and BC mixed aqueous solution;

[0060] 5) Mix 100 parts of PVA with 500 parts of deionized water, heat and stir at 95°C until completely dissolved, add 0.5 parts of dried stabilizer, 0.7 parts of plasticizer, 0.7 parts of lubricant, and 0.8 parts of compatibilizer, and continue heating and stirring at 95°C for 1 h to obtain a PVA mixed solution;

[0061] 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), and stirring and mixing at 95° C. for 1 h to obtain a PVA / PA / BC mixed solution;

[0062] 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method, the mixed solution was poured into a culture dish, and after air drying at room temperature for 60 min, the culture dish was placed in an oven at 60-70° C. and continued to dry for 48 h, and finally a PVA / PA / BC composite film with a thickness of 0.24 mm was obtained;

[0063] The preparation methods of the PVA / PA / BC composite films of Examples 2 to 5 are basically the same as those of Example 1, except that in the preparation step a) of Examples 2 to 5, the mass fractions of BC are 2 parts, 5 parts, 8 parts, and 10 parts, respectively, to prepare the PVA / PA / BC composite films of Examples 2 to 5, respectively.

[0064] For the PVA / PA / BC composite films of Examples 1 to 5, a cutter was used to process them into tensile test samples. The mechanical properties of the PVA / PA / BC composite films of Examples 1 to 5 were tested in groups according to the method of national standard GB / T 1040.1-2018; the water absorption properties of the PVA / PA / BC composite films of Examples 1 to 5 were tested in groups according to the method of national standard GB / T 1034-70, and the water contact angle of the PVA / PA / BC composite films of Examples 1 to 5 was tested; the limiting oxygen index of the PVA / PA / BC composite films of Examples 1 to 5 was tested according to the method of national standard GB / T 2406. The tensile test sample is a dumbbell-shaped specimen with a length of 50 mm, a gauge length of 30 mm, a middle width of 4 mm, and a thickness of 0.24 mm. The stretching speed is 20 mm / min, and at least 5 specimens are tested in each group. The average values ​​of the tensile strength, tensile modulus, and tensile elongation at break of the samples are taken. The results are as follows: Figure 1 As shown. The water absorption test sample is a 10 mm × 10 mm sample. The water absorption test is placed in deionized water at room temperature and 50% relative humidity for 24 hours and then the water absorption rate is weighed. At least 5 samples are tested in each group and the average value is taken. The contact angle test sample is a 3 cm × 1 cm sample. The contact angle meter is used to take pictures and analyze the software. At least 5 samples are tested in each group and the average value is taken. The volume of each drop of distilled water is set to 5 µl. The results are shown in Figure 2 The limiting oxygen index test sample size is 120 mm × 15 mm × 1.5 mm, and the results are shown in Figure 3 shown.

[0065] from Figure 1 , Figure 2 and Figure 3 It can be seen that as the amount of BC added increases, the tensile strength, elastic modulus and elongation at break of the PVA / PA / BC composite films of Examples 1 to 5 first increase and then decrease, the water resistance is improved, and the limiting oxygen index is also improved. Among these performance values, even the minimum value has an advantage over Comparative Example 1. Among them, compared with Comparative Example 1 without adding BC and PA, the tensile elongation at break is increased by about 63.4%, the limiting oxygen index is increased by 16%, and the water contact angle is increased by 3.1°. At the same time, the composite film does not swell in water. The microscopic surface of the PVA / PA / BC composite film of Example 3 ( Figure 4 )Comparison Example 1 ( Fig.21 ) has a rough surface, and the reinforcing BC particles are evenly dispersed. These results show that the addition of BC plays a reinforcing role, the addition of PA plays a key role in flame retardancy and plasticization, and the close interaction between BC and PA can improve the water resistance of PVA.

[0066] The mass fraction compositions of the PVA / PA / BC composite films of Examples 6 to 9 are shown in Table 2, and the PVA / PA / BC composite films of Examples 6 to 9 are numbered S1, S2, S3, and S4, respectively, and single factor experiments are performed.

[0067] Table 2

[0068]

[0069] In Examples 6 to 9, the stabilizer is antioxidant 1076, the plasticizer is xylitol, the lubricant is erucamide, and the compatibilizer is L-lysine triisocyanate.

[0070] The method for preparing the PVA / PA / BC composite film of Example 6 comprises the following steps:

[0071] 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0072] 2) Grind the BC particles and pass them through a 100-mesh sieve to obtain a BC sample with a particle size of 100 mesh;

[0073] 3) The BC sample obtained in step 2) was mixed with 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:8, stirred for 1 h, filtered, and then the BC was dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture. The solid-liquid mixture was fully stirred and the pH value was adjusted to 5.5-6 using the PA solution. The mixture was then ultrasonically treated for 15 min, filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900 ° C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC.

[0074] 4) adding 10 parts of PA solution and 5 parts of BC obtained in step 3) into 50 parts of deionized water, and ultrasonically treating for 20 min to obtain a pre-dispersed PA and BC mixed aqueous solution;

[0075] 5) Mix 100 parts of PVA with 400 parts of deionized water, heat and stir at 85°C until completely dissolved, add 1 part of dried stabilizer, 0.8 parts of plasticizer, 0.5 parts of lubricant, and 1 part of compatibilizer, and continue heating and stirring at 85°C for 1 h to obtain a PVA mixed solution;

[0076] 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), and stirring and mixing at 85° C. for 1.5 h to obtain a PVA / PA / BC mixed solution;

[0077] 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method, the mixed solution was poured into a culture dish, and after air drying at room temperature for 30 min, the culture dish was placed in an oven at 65° C. and continued to dry for 30 h, and finally a PVA / PA / BC composite film with a thickness of 0.10 mm was obtained;

[0078] The preparation methods of the PVA / PA / BC composite films of Examples 7 to 9 are basically the same as that of Example 1, except that in the preparation step 2) of Examples 7 to 9, the mesh sizes of BC are 1000 mesh, 2000 mesh, and 3000 mesh, respectively, to prepare the PVA / PA / BC composite films of Examples 7 to 9, respectively.

[0079] The same method as that of the PVA / PA / BC composite film of Example 1 was used to perform tensile tests, water absorption tests, water contact angle tests, and limiting oxygen index tests on the PVA / PA / BC composite films of Examples 6 to 9. The tensile test results are shown in FIG. Figure 5 As shown, the water absorption test and water contact angle test results are as follows Figure 6 shown.

[0080] from Figure 5 , Figure 6 and Figure 7 It can be seen that as the mesh number of BC increases, the tensile strength, elastic modulus, elongation at break, water resistance, and flame retardancy of the PVA / PA / BC composite films of Examples 6 to 9 first increase and then decrease. Among these performance values, even the minimum value has an advantage over Comparative Example 1. Among them, compared with Comparative Example 1 without adding BC and PA, the tensile elongation at break is increased by about 100%, the limiting oxygen index is increased by 20%, the water contact angle is increased by 8.5°, and the composite film does not swell in water. This shows that BC of different particle sizes has a strengthening effect on PVA films, and mechanical strengthening may be the particle strengthening effect of BC particles. Particles of appropriate size can synergize with PA to improve the flame retardant effect while improving toughness and water resistance.

[0081] For the BC with different mesh sizes in the PVA / PA / BC composite films of Examples 6 to 9, scanning electron microscopy observations were performed at 6 kV. Figure 8 SEM images of BC with different mesh sizes are shown. Figure 8 (ad) It can be seen that the particle size ranges of BC with different mesh sizes (100 mesh, 1000 mesh, 2000 mesh, 3000 mesh) in S1~S4 are approximately 13~15 μm, 8~10 μm, 5~7 μm and 2~4 μm.

[0082] The mass fraction compositions of the PVA / PA / BC composite films of Examples 10 to 13 are shown in Table 3, and the PVA / PA / BC composite films of Examples 10 to 13 are numbered K1, K2, K3, and K4, respectively, and single factor experiments are performed.

[0083] Table 3

[0084]

[0085] In Examples 10 to 13, the stabilizer is antioxidant 168, the plasticizer is lactitol, the lubricant is zinc stearate, and the compatibilizer is maleic anhydride grafted ethylene-octene copolymer.

[0086] The method for preparing the PVA / PA / BC composite film of Example 10 comprises the following steps:

[0087] 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0088] 2) Grind the BC particles and pass them through a 1000-mesh sieve to obtain a BC sample with a particle size of 1000 mesh;

[0089] 3) The BC sample obtained in step 2) was mixed with 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:9, stirred for 1 h, filtered, and then the BC was dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture. The solid-liquid mixture was fully stirred and the pH value was adjusted to 5.5-6 using the PA solution. The mixture was then ultrasonically treated for 18 min, filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900 ° C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC.

[0090] 4) adding 0 parts of PA solution and 5 parts of BC obtained in step 3) to 50 parts of deionized water, and ultrasonically treating for 20 min to obtain a pre-dispersed PA and BC mixed aqueous solution;

[0091] 5) Mix 100 parts of PVA with 550 parts of deionized water, heat and stir at 90°C until completely dissolved, add 0.3 parts of dried stabilizer, 0.6 parts of plasticizer, 0.7 parts of lubricant, and 0.3 parts of compatibilizer, and continue heating and stirring at 90°C for 1 h to obtain a PVA mixed solution;

[0092] 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), and stirring and mixing at 90° C. for 2 h to obtain a PVA / PA / BC mixed solution;

[0093] 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method. The mixed solution was poured into a culture dish, air-dried at room temperature for 40 min, and then the culture dish was placed in an oven at 65°C for further drying for 35 h to obtain a PVA / PA / BC composite film with a thickness of 0.4 mm.

[0094] The preparation method of the PVA / PA / BC composite films of Examples 11 to 13 is basically the same as that of Example 10, except that in the preparation step 4) of Examples 11 to 13, the mass fraction of PA is 5 parts, 10 parts, and 15 parts, respectively, to prepare the PVA / PA / BC composite films of Examples 11 to 13, respectively.

[0095] The same method as that of the PVA / PA / BC composite film of Example 1 was used to perform tensile test, water absorption test, water contact angle test and limiting oxygen index test on the PVA / PA / BC composite films of Examples 10 to 13. The tensile test results are shown in FIG. Fig. 9 As shown, the water absorption test and water contact angle test results are as follows Fig.10 As shown, the limiting oxygen index test results are as follows Fig.11 shown.

[0096] from Fig. 9 , Fig.10 and Fig.11 It can be seen that as the amount of PA added increases, the tensile strength, elastic modulus, and water contact angle of the PVA / PA / BC composite films of Examples 10 to 13 decrease, the elongation at break first increases and then decreases, and the water resistance is improved. Among these performance values, even the minimum value has an advantage over Comparative Example 1. Among them, compared with Comparative Example 1 without adding BC and PA, the tensile elongation at break increased by about 17%, the limiting oxygen index increased by 6.1%, and the water contact angle increased by 5.2°. At the same time, the composite films with added PA do not swell in water. These results show that PA plays a key role in toughening and flame retardancy in the PVA and BC composite system. The polar groups on the PA molecules can weaken the cohesion of the PVA molecular chain and improve the toughness of PVA; the phosphorus-containing groups of the PA molecules play a synergistic flame retardant role together with BC; the polar groups of the PA molecules also provide ionic bonding after the PVA molecules absorb water, maintaining the integrity of the material under high humidity.

[0097] The mass fraction compositions of the PVA / PA / BC composite films of Examples 14 to 17 are shown in Table 4, and the PVA / PA / BC composite films of Examples 14 to 17 are numbered E1, E2, E3, and E4, respectively.

[0098] Table 4

[0099]

[0100] In Examples 14 to 17, antioxidants 1010 and 1076 are used as stabilizers, erythritol is used as a plasticizer, hard amide is used as a lubricant, and glycidyl methacrylate grafted ethylene-octene copolymer is used as a compatibilizer.

[0101] The method for preparing the PVA / PA / BC composite film of Example 14 comprises the following steps:

[0102] 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0103] 2) Grind the BC particles and pass them through a 2000-mesh sieve to obtain a BC sample with a particle size of 2000 mesh;

[0104] 3) The BC sample obtained in step 2) was mixed with a 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:11, stirred for 1 h, filtered, and then the BC was dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture. The solid-liquid mixture was fully stirred and the pH value was adjusted to 5.5-6 using the PA solution. The mixture was then ultrasonically treated for 20 min, filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900 ° C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC.

[0105] 4) adding 10 parts of PA solution and 5 parts of BC obtained in step 3) into 50 parts of deionized water, and ultrasonically treating for 20 min to obtain a pre-dispersed PA and BC mixed aqueous solution;

[0106] 5) Mix 100 parts of PVA with 450 parts of deionized water, heat and stir at 95°C until completely dissolved, add 0.3 parts of dried stabilizer, 0.5 parts of plasticizer, 0.6 parts of lubricant, and 0.4 parts of compatibilizer, and continue heating and stirring at 95°C for 1 h to obtain a PVA mixed solution;

[0107] 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), and stirring and mixing at 95° C. for 1.2 h to obtain a PVA / PA / BC mixed solution;

[0108] 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method. The mixed solution was poured into a culture dish, air-dried at room temperature for 50 min, and then the culture dish was placed in an oven at 65°C for further drying for 24 h to obtain a PVA / PA / BC composite film with a thickness of 0.2 mm.

[0109] The preparation method of the PVA / PA / BC composite films of Examples 15 to 17 is basically the same as that of Example 14, except that in the preparation step 5) of Examples 15 to 17, the mass fractions of the stabilizer are 0.5 parts, 0.7 parts, and 1.0 parts, respectively, to prepare the PVA / PA / BC composite films of Examples 15 to 17, respectively.

[0110] The same method as that of the PVA / PA / BC composite film of Example 1 was used to perform tensile test, water absorption test, water contact angle test and limiting oxygen index test on the PVA / PA / BC composite films of Examples 14 to 17. The tensile test results are shown in FIG. Fig.12 As shown, the water absorption test and water contact angle results are as follows Fig.13 The limiting oxygen index results are shown in Fig.14 shown.

[0111] from Fig.12 , Fig.13 and Fig.14 It can be seen that as the amount of stabilizer added increases, the tensile strength, elastic modulus, and water contact angle of the PVA / PA / BC composite films of Examples 14 to 17 decrease, and the elongation at break first increases and then decreases, but the trend of change is not large, while the limiting oxygen index and water resistance are improved. Among these performance values, even the minimum value has an advantage over Comparative Example 1. Among them, compared with Comparative Example 1 without the addition of BC and PA, the tensile elongation at break increased by about 194%, the limiting oxygen index increased by 19.2%, and the water contact angle increased by 6.4°. At the same time, the composite films with the addition of BC and PA did not swell in water. This shows that adding a certain amount of stabilizer helps to improve the performance of the PVA composite film, but the improvement effect is not large. The stabilizer mainly improves the weather resistance and storage stability of the composite film, and the mechanical, water resistance and flame retardant properties of the composite film are mainly provided by PA and BC.

[0112] The mass fraction compositions of the PVA / PA / BC composite films of Examples 18 to 21 are shown in Table 5, and the PVA / PA / BC composite films of Examples 18 to 21 are numbered F1, F2, F3, and F4, respectively.

[0113] Table 5

[0114]

[0115] In Examples 18 to 21, the stabilizer is antioxidant 1790, the plasticizer is erythritol, the lubricant is stearyl zinc, and the compatibilizer is ethylene-vinyl acetate copolymer.

[0116] The method for preparing the PVA / PA / BC composite film of Example 18 comprises the following steps:

[0117] 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0118] 2) Grind the BC particles and pass them through a 3000-mesh sieve to obtain a BC sample with a particle size of 3000 mesh;

[0119] 3) The BC sample obtained in step 2) was mixed with 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:12, stirred for 1 h, filtered, and then the BC was dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture. The solid-liquid mixture was fully stirred and the pH value was adjusted to 5.5-6 with the PA solution. The mixture was then ultrasonically treated for 14 min, filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900 ° C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC.

[0120] 4) adding 10 parts of PA solution and 5 parts of BC obtained in step 3) into 50 parts of deionized water, and ultrasonically treating for 20 min to obtain a pre-dispersed PA and BC mixed aqueous solution;

[0121] 5) Mix 100 parts of PVA with 500 parts of deionized water, heat and stir at 90°C until completely dissolved, add 0.5 parts of dried stabilizer, 0.5 parts of plasticizer, 0.6 parts of lubricant, and 0.8 parts of compatibilizer, and continue heating and stirring at 90°C for 1 h to obtain a PVA mixed solution;

[0122] 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), and stirring and mixing at 90° C. for 1.8 h to obtain a PVA / PA / BC mixed solution;

[0123] 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method. The mixed solution was poured into a culture dish, air-dried at room temperature for 60 min, and then the culture dish was placed in an oven at 65°C for further drying for 48 h to obtain a PVA / PA / BC composite film with a thickness of 0.3 mm.

[0124] The preparation method of the PVA / PA / BC composite films of Examples 19 to 21 is basically the same as that of Example 18, except that in the preparation step 5) of Examples 19 to 21, the mass fraction of the plasticizer is 0.6 parts, 0.7 parts, and 0.8 parts, respectively, to prepare the PVA / PA / BC composite films of Examples 19 to 21, respectively.

[0125] The same method as that of the PVA / PA / BC composite film of Example 1 was used to perform tensile test, water absorption test, water contact angle test and limiting oxygen index test on the PVA / PA / BC composite films of Examples 18 to 21. The tensile test results are shown in FIG. Fig.15 As shown, the water absorption test and water contact angle results are as follows Fig.16 As shown, the limiting oxygen index test results are as follows Fig.17 shown.

[0126] from Fig.15 , Fig.16 and Fig.17 It can be seen that as the amount of plasticizer added increases, the tensile strength of the PVA / PA / BC composite films of Examples 18 to 21 decreases, the elastic modulus, elongation at break and water contact angle increase, and the water resistance and flame retardancy are improved. Among these performance values, even the minimum value has an advantage over Comparative Example 1. Among them, compared with Comparative Example 1 without adding BC and PA, the tensile elongation at break increased by about 195%, the limiting oxygen index increased by 23.4%, and the water contact angle increased by 4.4°. At the same time, the composite films with added PA do not swell in water. This shows that the presence of plasticizer can further enhance the toughening effect of PA. The plasticizer itself contains polar groups, which can plasticize PVA molecules together with PA; and the plasticized PVA can make the BC particles more evenly and stably dispersed, thereby improving the mechanical, water resistance and flame retardant properties of PVA.

[0127] The mass fraction compositions of the PVA / PA / BC composite films of Examples 22 to 24 are shown in Table 6, and the PVA / PA / BC composite films of Examples 22 to 24 are numbered O1, O2, O3, and O4, respectively.

[0128] Table 6

[0129]

[0130] In Examples 22 to 24, antioxidants 1790 and 1010 are used as stabilizers, lactitol is used as a plasticizer, hard amide is used as a lubricant, and maleic anhydride grafted ethylene-octene copolymer is used as a compatibilizer.

[0131] The method for preparing the PVA / PA / BC composite film of Example 25 comprises the following steps:

[0132] 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0133] 2) Grind the BC particles and pass them through a 100-mesh sieve to obtain a BC sample with a particle size of 100 mesh;

[0134] 3) The BC sample obtained in step 2) was mixed with 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:10, stirred for 1 h, filtered, and then the BC was dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture. The solid-liquid mixture was fully stirred and the pH value was adjusted to 5.5-6 using the PA solution. The mixture was then ultrasonically treated for 19 min, filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900°C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC.

[0135] 4) 10 parts of PA solution and 10 parts of BC obtained in 3) were added to 50 parts of deionized water, and ultrasonically treated for 20 min to obtain a pre-dispersed PA and BC mixed aqueous solution;

[0136] 5) Mix 100 parts of PVA with 500 parts of deionized water, heat and stir at 95°C until completely dissolved, add 0.6 parts of dried stabilizer, 0.7 parts of plasticizer, 0.7 parts of lubricant, and 0.3 parts of compatibilizer, and continue heating and stirring at 95°C for 1 h to obtain a PVA mixed solution;

[0137] 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), and stirring and mixing at 95° C. for 1.5 h to obtain a PVA / PA / BC mixed solution;

[0138] 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method. The mixed solution was poured into a culture dish, air-dried at room temperature for 50 min, and then the culture dish was placed in an oven at 65°C for further drying for 36 h to obtain a PVA / PA / BC composite film with a thickness of 0.45 mm.

[0139] The preparation method of the PVA / PA / BC composite films of Examples 23 to 25 is basically the same as that of Example 22, except that in the preparation step 5) of Examples 23 to 25, the mass fraction of the compatibilizer is 0.5 part, 0.8 part, and 1.0 part, respectively, to prepare the PVA / PA / BC composite films of Examples 22 to 25, respectively.

[0140] The same method as that of the PVA / PA / BC composite film of Example 1 was used to perform tensile test, water absorption test, water contact angle test and limiting oxygen index test on the PVA / PA / BC composite films of Examples 22 to 25. The tensile test results are shown in FIG. Fig.18 As shown, the water absorption test and water contact angle results are as follows Fig.19 As shown, the limiting oxygen index test results are as follows Fig. 20 shown.

[0141] from Fig.18 , Fig.19 and Fig. 20 It can be seen that as the amount of compatibilizer added increases, the tensile strength, elastic modulus, elongation at break and water contact angle of the PVA / PA / BC composite films of Examples 22 to 25 first increase and then decrease, and the water resistance is improved. Among these performance values, even the minimum value has an advantage over Comparative Example 1. Among them, compared with Comparative Example 1 without adding BC and PA, the tensile elongation at break increased by about 171%, the limiting oxygen index increased by 17.7%, and the water contact angle increased by 6.8°. At the same time, the composite films with added PA did not swell in water. These results show that the increase in BC particles will increase the thickness of the film; the addition of compatibilizer is beneficial to the improvement of the surface interface between PVA and PA, PVA and BC, and PA and BC, and ultimately improves the performance of the PVA composite film.

[0142] The PVA film of Comparative Example 1 does not add PA and BC, and its mass proportions are as follows: 100 parts of PVA, 0 parts of PA, 0 parts of BC, 0.5 parts of stabilizer, 0.7 parts of plasticizer, 0.7 parts of lubricant, and 0.8 parts of compatibilizer, wherein the stabilizer is used, the plasticizer is used, the lubricant is maleic anhydride, and the coupling agent is titanate coupling agent.

[0143] The preparation method of the PVA film of Comparative Example 1 comprises the following steps:

[0144] 1) After weighing the raw materials of each component by mass, put PVA, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use;

[0145] 2) Mix 100 parts of PVA with 500 parts of deionized water, heat and stir at 95°C until completely dissolved, add 0.5 parts of dried stabilizer, 0.7 parts of plasticizer, 0.7 parts of lubricant, and 0.8 parts of compatibilizer, and continue heating and stirring at 95°C for 1 h to obtain a PVA mixed solution;

[0146] 3) The PVA solution obtained in step 2) was prepared into a composite film by a solution casting method. The mixed solution was poured into a culture dish. After air-drying at room temperature for 45 min, the culture dish was placed in an oven at 65°C and continued to dry for 36 h, and finally a PVA film with a thickness of 0.25 mm was obtained.

[0147] The same method as the PVA film of Example 1 was used to perform tensile test, water absorption test, water contact angle, limiting oxygen index and surface morphology test on the PVA film of Comparative Example 1, and the elongation at break was 86.6%, the water contact angle was 64.3°, and the limiting oxygen index was 18.4%. Its surface was relatively smooth, and no reinforcing particles were found.

Claims

1. A flame retardant multifunctional polyvinyl alcohol (PVA) / phytic acid (PA) / biochar (BC) composite film, characterized in that: The mass fraction is as follows: 100 parts of PVA, 5-15 parts of PA, 2-10 parts of BC, 0.3-1 parts of stabilizer, 0.5-0.8 parts of plasticizer, 0.5-0.7 parts of lubricant, and 0.3-1 parts of compatibilizer. The preparation method of the PVA / PA / BC composite film comprises the following steps: 1) After weighing the raw materials of each component by mass, put PVA, BC, stabilizer, plasticizer, lubricant and compatibilizer into an oven for drying at a temperature of 60-105°C. After being absolutely dry, take them out for use; 2) Grind the BC particles and pass them through 100 mesh, 1000 mesh, 2000 mesh and 3000 mesh sieves to obtain BC samples with different particle sizes; 3) The BC samples with different particle sizes obtained in step 2) were mixed with 0.5 g / ml potassium hydroxide solution at a mass volume ratio of 1:8-12, stirred for 1-2 h, filtered, and then dried. The dried BC was then placed in a 70% PA solution to obtain a solid-liquid mixture, which was fully stirred and the pH value of the solid-liquid mixture was adjusted to 5.5-6 using the PA solution. The mixture was then ultrasonically treated for 10-20 min, the solid-liquid mixture was filtered, washed with deionized water until neutral, dried, placed in a muffle furnace, and treated at 900°C for 0.5 h in a nitrogen atmosphere to obtain an activated porous BC; 4) adding 5 to 15 parts of PA solution and 2 to 10 parts of BC obtained in step 3) to 50 parts of deionized water, and ultrasonically treating for 10 to 30 minutes to obtain a pre-dispersed PA and BC mixed aqueous solution; 5) Mix 100 parts of PVA with 400-600 parts of deionized water, heat and stir at 85-95°C until completely dissolved, add 0.3-1 parts of dried stabilizer, 0.5-0.8 parts of plasticizer, 0.5-0.7 parts of lubricant, and 0.3-1 parts of compatibilizer, and continue heating and stirring at 85-95°C for 1-2 h to obtain a PVA mixed solution; 6) adding the pre-dispersed PA and BC mixed aqueous solution obtained in step 4) to the PVA mixed solution obtained in step 5), stirring and mixing at 85-95° C. for 1-2 h to obtain a PVA / PA / BC mixed solution; 7) The PVA / PA / BC mixed solution obtained in step 6) was prepared into a composite film by a solution casting method. The mixed solution was poured into a culture dish, and after air-drying at room temperature for 30 to 60 min, the culture dish was placed in an oven at 65°C and continued to dry for 20 to 48 h to finally obtain a PVA / PA / BC composite film with a thickness of 0.05 to 0.50 mm.

2. The composite film according to claim 1, characterized in that The PVA model is at least one of 0599, 1799, and 2499, and its polymerization degree is 500, 1700, and 2400 respectively, and its alcoholysis degree is 99 mol%.

3. The composite film according to claim 1, characterized in that The BC is sourced from one or a combination of two or more of pine, poplar, eucalyptus, oak and bamboo, and is pyrolyzed at 300-500° C. in an oxygen-deficient environment for 3-5 h, and then washed, dried and crushed to obtain particles.

4. The composite film according to claim 1, characterized in that The PA is a PA aqueous solution with a concentration of 70%.

5. The composite film according to claim 1, characterized in that The stabilizer is one of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant 1790, or a combination of two or more thereof.

6. The composite film according to claim 1, characterized in that: The plasticizer is at least one of sorbitol, xylitol, erythritol and lactitol.

7. The composite film according to claim 1, characterized in that The lubricant is at least one of calcium stearate, erucamide, stearamide and zinc stearate.

8. The composite film according to claim 1, characterized in that The compatibilizer is at least one of glycidyl methacrylate, L-lysine triisocyanate, maleic anhydride grafted ethylene-octene copolymer, glycidyl methacrylate grafted ethylene-octene copolymer and ethylene-vinyl acetate copolymer.

9. The composite film according to claim 1, characterized in that: In step 2), BC screening starts from the smallest pores, in the order of 3000 mesh, 2000 mesh, 1000 mesh and 100 mesh; in step 3), the heating rate of the muffle furnace is 5~20℃ / min.

Citation Information

Patent Citations

  • Preparation method of degradable water-retaining mulch film

    CN109197283A

  • Preparation method of bio-based flame-retardant and light-aging-resistant PVA (Polyvinyl Alcohol) composite material

    CN113185873A

  • Starch / polyethylene degradable film and preparation method thereof

    CN114561044A

  • Polylactic acid / polycaprolactone / plant carbon black composite material and preparation method thereof

    CN115322543A

  • Formula of polyvinyl alcohol flame-retardant film and preparation method of polyvinyl alcohol flame-retardant film

    CN117004158A

Cited By

  • High-barrier flame-retardant food packaging film and preparation method thereof

    CN120365676A

  • Degradable rubber composition and preparation process thereof

    CN121914470A